Analysis of material removal of Inconel 718 cylinder using magnetic abrasive finishing process assisted with chemical etching. (2022) - Kumar, Arun; Kumar, Harish
Abstract: Application of Inconel 718 cylinders have been uprising with the up gradation of requirement of super alloys in this advance technological world. Although Inconel 718 possesses superior mechanical properties resulting into excellent performance in extreme environmental conditions but on the other hand make it difficult to machine and finish with available machining processes. This investigation has been used for the analysis of material removal of Inconel 718 cylinder using magnetic abrasive finishing process assisted with chemical etching. Finishing process has been conducted on 155 mm long and 5.7 mm thick Inconel 718 cylinder under specified investigating variable parameters such as duration of processing, work pole gap, abrasive weight percentage, and size of abrasive particles and concentration of etchant keeping certain factors as constant like rotational speed, etching temperature. Impact of processing variables represent through surface microstructure.